The Physical Environment of Sarawak - Harwant, Singh (UNIMAS Publisher, 2012)
A variety of information on the natural environment has accumulated over the decades since the inception of Sarawak as a formal entity in the modern sense over the last two centuries. This entails the evolution of a state whose organs have come to play the premier role in the investigation and elucidation of the natural environment. This substantial amount of information and accounts on various aspects of the natural environment has been generated due to the commendable efforts of various workers involved with the above.This publication is an attempt at coalescing information from various sources to provide a comprehensive, coherent, multi-faceted account of natural environment of Sarawak.